A multiparameter analysis of a select repertoire of British punk rock of the first wave, 1976-1979 - Van Zyl, Willem Adriaan (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Mus.)--University of Stellenbosch, 2006.